TEORI HUKUM JA’FARIYAH (Analisis Historis Mazhab Fikih Ja’far As-Shadiq Dan Implikasinya Pada Produk Hukumnya) - Hamdi, Bahrul; Saputra, Ayen (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2018)
There are two major streams in Islam which up to now have a very significant influence in the Islamic community, namely the Shiite sect and the Ahlus Sunnah wa al-Jama'ah sect. Apart from differences in theological discourse, the differences between these two sects also touch the jurisdictions (fiqh). The most obvious differences in fiqh products, for example, appear in the permissibility of marriage if married (contract marriage). Some non-fundamental differences occur in other discourses, such as in prayer, azan, etc. This article intends to discuss legal theory that animates legal products in the Ja'fari school. The presence of Imam Ja'far in his capacity as a respected founder of the Ja'fari school, both Sunni and Shiite, will be discussed specifically in this paper. In addition, this article also discusses a number of fiqh Ja'fari products which may be fundamentally different from the Sunni fiqh products, including about khumus and mut'ah. The legal sources used in the Ja'fari school are not much different from the legal sources used in Sunni schools, which revolve around the Qur'an, Sunnah, Ijma', and Intellect. Although there is an understanding of the different definitions of the sources of the law, this does not indicate that Syi'ah and Sunni have different principles in determining the law.